2017
DOI: 10.1108/er-02-2017-0039
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the living wage in UK local government

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Several findings are apparent in the table, which relate to the question of the relationship between trade unionism and civil regulation. First, the table indicates that senior managers and owners have been the primary force behind the introduction of the Living Wage even where trade unions are present; a finding that echoes those of case studies of the introduction of the Living Wage (Johnson, ; Lopes and Hall, ). Moreover, in LWEs with trade unions, specialist managers in HR and corporate social responsibility (CSR) are also likely to have played an active part in the adoption of the standard, reflecting the fact that both sets of actors tend to be found in larger organisations with more formal, differentiated structures of management.…”
Section: Trade Union Support For and Involvement In Living Wage Accrementioning
confidence: 76%
See 3 more Smart Citations
“…Several findings are apparent in the table, which relate to the question of the relationship between trade unionism and civil regulation. First, the table indicates that senior managers and owners have been the primary force behind the introduction of the Living Wage even where trade unions are present; a finding that echoes those of case studies of the introduction of the Living Wage (Johnson, ; Lopes and Hall, ). Moreover, in LWEs with trade unions, specialist managers in HR and corporate social responsibility (CSR) are also likely to have played an active part in the adoption of the standard, reflecting the fact that both sets of actors tend to be found in larger organisations with more formal, differentiated structures of management.…”
Section: Trade Union Support For and Involvement In Living Wage Accrementioning
confidence: 76%
“…A number of insightful case studies of Living Wage campaigns have been published in recent years, which focus on a single or a small number of organisations that have adopted the Living Wage, often as a result of trade union pressure (Johnson, ; Lopes and Hall, ; Prowse and Fells, , ). The research reported hereafter adopted a different, though complementary approach, centrepiece of which was a population survey of all accredited LWEs carried out in late 2016.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Building on Tattersall's (2005) typology of union-community engagement they highlight the strategic nature of effective campaigning. For its part Johnson (2017) evaluates the implications of the "real" LW as an annual pay rise for lower paid workers in four English local authorities. His findings highlight its positive impact on lower paid workers and the consequent compression of wage differentials.…”
mentioning
confidence: 99%